Deteksi Dini Tindakan Kekerasan Pada Remaja - Suryati; Oktavianto, Eka (Jurnal Indonesia Sehat, 2025)
Background: Violence experienced by children often occurs in the child's immediate environment and it is not uncommon for the perpetrator to be someone close to them or someone the child knows. Violence against children can also be carried out by other children. There are many reasons given, but most of them stem from the perpetrator's inability to manage/control his emotions or anger, as well as a lack of understanding of the impact of these acts of violence on the quality of the child's development in the long term. Objective: The aim of this research is to detect early as a first step in screening for incidents of sexual violence that have occurred among teenagers, especially at the Al-Ihsan Baleendah Modern Islamic Boarding School, Bandung. Method: This type of research is quantitative descriptive with a sampling technique using simple random sampling. The sample in this study was 45 teenagers. The instrument used was the Child Abuse Screening Tool- Children Instrument (ICAST-C). The data analysis used was univariate with descriptive analysis. Results: The results of the study stated that of the 45 teenagers, 29 respondents experienced psychological violence, 18 respondents experienced physical violence and 15 respondents experienced neglect. Conclusion: The conclusion from this research is that there are still incidents of violence against children, be it psychological violence, physical violence or neglect.